Pengaruh Perencanaan Pajak terhadap Manajemen Laba pada PT. Merapi Utama Pharma Medan - Andini, Selly; Januri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to investigate the impact of tax planning on revenue management practices at PT. Merapi Utama Pharmacy, Medan. This research uses quantitative and correlational analysis methods. The scope of this research is limited to the period 2018 to 2022. The data analysis method used in this research is the simple linear regression analysis method. The findings of this research show that tax planning has a positive correlation and influence on laboratory management, thus indicating that improving tax planning will also lead to improved laboratory management. The findings of this research are consistent with rational choice theory and accounting theory. A company needs a superior competitive advantage compared to its business competitors in order to achieve high profitability. One of these advantages lies in the company's ability to manage finances effectively, which in turn will ensure long-term business continuity. The sustainability of this business can be measured from the level of profitability obtained. These are the factors that encourage management to engage in the presentation and reporting of laboratory information, also known as